High fastness dyeing and finishing process of polyester fabric

CN122980241APending Publication Date: 2026-10-27SHAOXING ZHIREN PRINTING & DYEING
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611476646.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-22
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

已有公开技术还提出了分散染料组合物和涤纶纤维染色方法,但仍存在分散稳定、染料迁移、浮色去除和织物结构保持难以同时兼顾的不足

Benefits of technology

1.本发明采用分散染料-磺酸钠基聚酯-聚醚共聚物复合分散颗粒,通过预分散和湿法研磨使分散染料与磺酸钠基聚酯-聚醚共聚物形成粒径受控的复合分散颗粒,能够降低染浴中染料颗粒团聚倾向,同时避免过强分散保护阻碍染料迁移,有利于改善涤纶织物染色均匀性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122980241A_ABST
    Figure CN122980241A_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of textile dyeing and finishing, and provides a high-fastness dyeing and finishing process for polyester fabric. The present application is characterized by the following: the mass ratio of the dispersed dye and the sodium sulfonate-based polyester-polyether copolymer is 100:10-80, the D50 of the dispersed dye-sodium sulfonate-based polyester-polyether copolymer composite dispersion particle is 100-350 nm, and the PDI is 0.10-0.35; the dyeing bath is adjusted by acetic acid / anhydrous sodium acetate; the pH, bath ratio, temperature rising rate, dyeing temperature, cleaning and setting conditions of the dyeing bath are controlled; a dyeing and finishing process that takes into account dispersion stability, dye migration and color removal is formed; the polyester fabric has high soaping fastness and rubbing fastness; the problem that dispersion stability, dyeing uniformity, color removal and fabric structure integrity are difficult to be considered simultaneously is solved; and the present application is suitable for high-fastness dyeing and finishing of polyester fabric.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of textile dyeing and finishing technology, specifically to a high-fastness dyeing and finishing process for polyester fabrics. Background Technology

[0002] Polyester fabrics are widely used in apparel, home textiles, industrial textiles, and functional textile materials due to their high strength, good dimensional stability, ease of care, and wide applicability. Polyester fibers have a dense molecular chain structure and strong hydrophobicity, typically requiring disperse dyes at high temperatures for dyeing. The dispersion state of dye particles in the dye bath, the ability of dye to migrate into the fiber interior, the degree of surface dye removal after dyeing, and the thermal stability during finishing all affect the color uniformity and fastness of the final fabric. For medium-dark polyester fabrics, there are interdependent relationships between dye dosage, dye bath pH, ​​heating rate, heat preservation conditions, washing intensity, and setting conditions. A narrow process window can easily lead to color variations, staining, stiffening of the hand feel, or insufficient fastness. Therefore, developing dyeing and finishing processes that balance dispersion stability, dye migration, surface dye removal, and fabric structure preservation is of great significance for improving the quality of polyester fabrics and expanding their applications.

[0003] Existing polyester disperse dye dyeing technologies typically improve dye dispersion and uptake by increasing dispersants, auxiliaries, or dyeing temperatures. However, excessively strong dispersion protection, while preventing dye particle aggregation, may reduce the efficiency of dye migration from the dye bath to the polyester fibers. Simply increasing dyeing temperature, extending holding time, or increasing dye dosage can easily lead to decreased dispersion system stability, increased floating dye, and a heavier burden on subsequent washing. For example, Chinese patent CN111648140A discloses a polyester fabric dyeing process that improves the dispersion and color fastness of disperse dyes in water through dispersants, auxiliaries, and post-dyeing treatments. However, it still mainly relies on the combination of multiple auxiliaries and post-treatment to coordinate dispersion, uptake, and fastness issues. Existing technologies have also proposed disperse dye compositions and polyester fiber dyeing methods, but they still suffer from the inability to simultaneously address dispersion stability, dye migration, floating dye removal, and fabric structure maintenance. Summary of the Invention

[0004] The purpose of this invention is to provide a high-fastness dyeing and finishing process for polyester fabrics, which solves the current pain point that it is difficult to simultaneously achieve dispersion stability and dye migration uniformity, and floating color removal and fabric structural integrity.

[0005] This invention achieves a synergistic balance between dyeing uniformity, dispersion stability, and color fastness by controlling the mass ratio of disperse dye to sodium sulfonate-based polyester-polyether copolymer, the D50 and PDI of the composite disperse particles, and coordinating the disperse dye-sodium sulfonate-based polyester-polyether copolymer composite disperse particles with an acetic acid / anhydrous sodium acetate weak acid buffer system, while simultaneously controlling the heating, washing, and setting processes. This ensures that dispersion protection does not excessively hinder dye migration, and floating color removal does not excessively damage the fabric structure.

[0006] To achieve the above objectives, the present invention provides the following technical solution: A high-fastness dyeing and finishing process for polyester fabrics includes the following steps: S1. Provides an aqueous dyeing and finishing composition comprising disperse dye-sodium sulfonate-polyester-polyether copolymer composite disperse particles, acetic acid, anhydrous sodium acetate, and deionized water, wherein the mass ratio of disperse dye to sodium sulfonate-polyether copolymer in the composite disperse particles is 100:10-80, the D50 of the composite disperse particles is 100-350 nm, and the PDI is 0.10-0.35; S2. Preparation of the dye bath: The aqueous dyeing and finishing composition is added to deionized water, and the pH of the dye bath is adjusted to 4.50-5.80 using acetic acid and anhydrous sodium acetate, so that the amount of disperse dye used is 0.10-6.00 wt% of the polyester fabric mass; S3. Dyeing: Place the polyester fabric in the dye bath, with a bath ratio of 1:5 to 1:15 (based on the ratio of the mass of the polyester fabric to the mass of the dye bath), and heat to 120-135℃ at a rate of 0.80-2.00℃ / min, and hold for 30-60 minutes. S4. Cleaning: After cooling, drain the liquid and clean with deionized water at 60-90℃ for 5-20 minutes; S5. Drying and setting: Dry at 100-130℃ for 1-5 minutes, then set at 160-185℃ for 20-90 seconds to obtain dyed and finished polyester fabric.

[0007] S3 is performed in a pressure-resistant dyeing device.

[0008] Furthermore, the disperse dye is selected from one or more of Disperse Red 60, Disperse Blue 56, Disperse Blue 79, and Disperse Orange 30; the sodium sulfonate-based polyester-polyether copolymer is obtained by transesterification and polycondensation of dimethyl terephthalate, sodium 5-sulfonate dimethyl isophthalate, ethylene glycol, and polyethylene glycol.

[0009] Furthermore, the disperse dye-sodium sulfonate-polyester-polyether copolymer composite dispersed particles are prepared through the following steps: A1. Raw material preparation: Mix 100 parts by weight of disperse dye, 10-80 parts by weight of sodium sulfonate-based polyester-polyether copolymer, and deionized water, so that the solid content, based on the total mass of the disperse dye and the sodium sulfonate-based polyester-polyether copolymer as a percentage of the total mass of the mixture, is 10.00-35.00 wt%. A2. pH adjustment: Add acetic acid and anhydrous sodium acetate to adjust the pH of the system to 5.00-7.00; A3. Pre-dispersion: Shear dispersion at 1000-8000 rpm for 0.50-2.00 h at 15-45℃; A4. Wet grinding: Using zirconia beads with a particle size of 0.10-1.00 mm as the grinding media, wet grinding is carried out at 15-45℃ and a linear velocity of 5-15 m / s for 0.50-4.00 h. A5. Post-treatment: Filter by 100-400 mesh to obtain an aqueous dispersion of disperse dye-sodium sulfonate-polyether copolymer composite dispersion particles; A6. Endpoint Criteria: The D50 of the composite dispersed particles in the aqueous dispersion is 100-350 nm, and the PDI is 0.10-0.35. The obtained aqueous dispersion is used for the preparation of aqueous dyeing and finishing compositions and dye baths.

[0010] Furthermore, the sodium sulfonate-based polyester-polyether copolymer is prepared by the following steps: B1. Raw material preparation: Dimethyl terephthalate and sodium 5-sulfonate dimethyl isophthalate are mixed at a molar ratio of 70-95:5-30, wherein the sum of their molar parts is 100; ethylene glycol is added, wherein the molar ratio of ethylene glycol to the total molar amount of dimethyl terephthalate and sodium 5-sulfonate dimethyl isophthalate is 1.60-2.40:1; polyethylene glycol is added, wherein the number average molecular weight of polyethylene glycol is 400-4000 g / mol, and the amount of polyethylene glycol used is 5.00-30.00 wt% of the total mass of dimethyl terephthalate and sodium 5-sulfonate dimethyl isophthalate. B2. Catalyst addition: Add tetrabutyl titanate in an amount of 0.02-0.20 wt% of the total mass of dimethyl terephthalate, sodium isophthalate 5-sulfonate, ethylene glycol, and polyethylene glycol in step B1. B3. Transesterification reaction: Under nitrogen protection, the reaction is carried out at 160-200℃ for 2.00-5.00h. Methanol is collected. When the amount of methanol distilled reaches 70.00-95.00% of the theoretical methanol distillation amount calculated based on the complete transesterification of the methyl groups of dimethyl terephthalate and sodium isophthalate 5-sulfonate, the polycondensation reaction begins. B4. Polycondensation reaction: Heat to 210-245℃ and react for 1.00-4.00 h under an absolute pressure of 100-5000 Pa in the reactor; B5. Post-processing: The discharged material is cooled, pulverized, and dried at 60-90℃ and 0.001-0.010MPa for 4.00-12.00h to obtain the sodium sulfonate-based polyester-polyether copolymer; B6. Composition parameters: Based on the molar ratio of dimethyl terephthalate and sodium 5-sulfonate dimethyl isophthalate, the theoretical structural unit content derived from sodium 5-sulfonate dimethyl isophthalate is 5.00-30.00 mol.

[0011] The sodium sulfonate-based polyester-polyether copolymer is used to form a composite dispersion system with disperse dyes and is not used as a fiber-forming raw material for polyester fibers. This application does not use the intrinsic viscosity of spinning-grade polyethylene terephthalate as a technical indicator for this copolymer. The suitability of the copolymer in this dyeing and finishing process is evaluated in conjunction with the D50, PDI, dispersion retention, and corresponding dyeing and finishing results of the composite dispersion particles it participates in forming. The structural unit content mentioned in B6 is a theoretical structural unit content calculated based on the raw material molar ratio, and not a value obtained from actual measurement of the final copolymer composition.

[0012] Furthermore, in S2, the amount of disperse dye used is 0.50-4.00 wt% of the polyester fabric mass.

[0013] Furthermore, in S2, the pH of the dye bath is 4.80-5.50.

[0014] Furthermore, in S3, the liquor ratio is 1:6-1:10, the temperature is increased to 125-132℃ at 1.00-1.50℃ / min, and held for 35-50min.

[0015] Furthermore, after S4 cleaning, a reduction cleaning is performed, which uses 0.50-2.00 g / L sodium dithionite and 0.50-2.00 g / L sodium hydroxide, and is treated at 70-85℃ for 5-20 min.

[0016] Furthermore, the weight of the polyester fabric is 50-300 g / m².

[0017] Furthermore, in S5, the setting temperature is 165-178℃, and the setting time is 30-60s.

[0018] Furthermore, the color fastness to washing of the polyester fabric obtained after dyeing and finishing is determined to be grade 4 or 4-5 according to GB / T 3921-2008, and the color fastness to rubbing is determined to be grade 4 or 4-5 for dry rubbing and grade 3 or 4 for wet rubbing according to GB / T 3920-2008. The above grades are recorded according to the standard fixed range, and the color fastness grade code is not used as a continuous numerical calculation arithmetic mean.

[0019] Furthermore, the polyester fabric is a woven fabric, knitted fabric, or nonwoven fabric. Before entering the dye bath in step S3, it undergoes desizing, scouring, or pre-forming treatment. The treated polyester fabric is then used as the dyeing target in step S3.

[0020] Furthermore, after the heat preservation in step S3, the dye bath temperature is reduced at a rate of 1-3℃ / min and the liquid is drained; the polyester fabric after draining is washed with deionized water at 60-90℃ for 5-20 minutes, and the number of washes is 1-3 times. The washed polyester fabric then enters step S5.

[0021] Furthermore, after completing the reduction cleaning, the polyester fabric is washed with deionized water at 50-80℃ for 5-15 minutes, and then the washed polyester fabric enters step S5.

[0022] Furthermore, in step S5, one of hot air drying, infrared drying, or pad drying is used to dry the polyester fabric after cleaning or reduction cleaning in step S4 at 100-130℃ for 1-5 minutes, and then set it at 160-185℃ for 20-90 seconds to obtain the set polyester fabric.

[0023] Furthermore, for the polyester fabrics that have been set in step S5, the color fastness to washing was determined according to GB / T3921-2008, and the color fastness to dry rubbing and wet rubbing was determined according to GB / T3920-2008. The color fastness grades to washing, dry rubbing, and wet rubbing were recorded, and the recorded grades were used as the color fastness evaluation index for dyed and finished polyester fabrics.

[0024] As a concept of this invention, the present invention employs a design that synergistically controls the disperse dye-sodium sulfonate-based polyester-polyether copolymer composite dispersed particles with an acetic acid / anhydrous sodium acetate buffer dye bath. This design primarily aims to achieve a synergistic balance between the stability of the dispersion system and the dyeing uniformity of polyester fabrics. In existing technologies, to enhance the dispersion and protection of disperse dyes in the dye bath, dispersants are typically added or the particle surface protection is strengthened. However, excessive protection can restrict dye migration to polyester fibers. To enhance dye migration and dyeing depth, temperatures are often increased, heat preservation is prolonged, or the dye dosage is increased. However, these methods easily cause dye particle agglomeration and increase floating dye. This invention, by pre-dispersing the sodium sulfonate-based polyester-polyether copolymer and disperse dye through wet milling to form composite dispersed particles, and by using acetic acid and anhydrous sodium acetate to regulate the weakly acidic dye bath environment, establishes a continuous and coordinated relationship between particle dispersion, dye migration, fiber adsorption, and subsequent washing, thereby balancing dye bath stability, dyeing uniformity, and color fastness maintenance.

[0025] The composite disperse particles of disperse dye-sodium sulfonate-polyester-polyether copolymer mainly address the issues of particle size control and anti-agglomeration of disperse dyes in aqueous dye baths, while the acetic acid / anhydrous sodium acetate buffer system mainly addresses the issues of pH stability in the dye bath and regulation of the dye migration environment. If only the dispersion protection of the sodium sulfonate-polyester-polyether copolymer is relied upon, although particle stability is enhanced, dye release and migration into the polyester fiber may be limited. If only weak acid buffering and high-temperature dyeing conditions are relied upon, dye migration can be improved, but insufficient protection of the particle surface can easily lead to agglomeration and increased floating dye. This invention, through the matching ratio of disperse dye to sodium sulfonate-polyester-polyether copolymer, wet milling particle size control, and acetic acid / anhydrous sodium acetate buffer control, enables the composite disperse particles to maintain moderate stability in the dye bath and preserve the dye's ability to migrate into the fiber, ultimately balancing the inherently contradictory properties of dispersion stability and dyeing uniformity.

[0026] Beneficial technical effects 1. This invention uses disperse dye-sodium sulfonate-polyester-polyether copolymer composite dispersed particles. Through pre-dispersion and wet milling, the disperse dye and sodium sulfonate-polyester-polyether copolymer form composite dispersed particles with controlled particle size. This can reduce the tendency of dye particles to agglomerate in the dye bath, while avoiding excessive dispersion protection that hinders dye migration, which is beneficial to improving the dyeing uniformity of polyester fabrics.

[0027] 2. This invention adjusts the pH of the dye bath using acetic acid and anhydrous sodium acetate, maintaining the dye bath in a weakly acidic environment suitable for dyeing polyester fibers with disperse dyes. This buffers local pH fluctuations during the dyeing process, reduces the risk of dye dispersion imbalance and color variations, thereby improving the process stability of the dyeing and finishing process.

[0028] 3. This invention combines and controls the heating rate, dyeing temperature, holding time, washing temperature, and washing time to ensure continuous connection between dye migration, fiber adsorption, and floating color removal. This can improve color fastness while reducing the adverse effects of excessive washing on fabric structure and hand feel.

[0029] 4. The present invention further controls the drying and setting conditions to enable the dyed and finished polyester fabrics to obtain high color fastness to washing, dry rubbing and wet rubbing while maintaining dimensional stability and uniform surface condition, making it suitable for industrial dyeing and finishing applications of medium and dark polyester fabrics. Attached Figure Description

[0030] Figure 1 This is a statistical graph showing the effect of sodium sulfonate-based polyester-polyether copolymer dosage on the dispersion retention rate over 24 hours.

[0031] Figure 2 This is a statistical graph showing the effect of dye bath pH on dyeing uniformity in Example 1.

[0032] Figure 3 This is a statistical graph showing the effect of composite dispersed particles D50 on the 24-hour dispersion retention rate and dyeing uniformity in Example 1.

[0033] Figure 4 This is a statistical graph showing the effect of the shaping temperature on the fracture strength retention rate in Example 1.

[0034] Figure 5 The chart shows the 24-hour dispersion retention rate of Example 1, Comparative Example 9, and Comparative Example 11.

[0035] Figure 6 The pH change curves during the dye bath process of Example 1, Comparative Example 3, and Comparative Example 11 are shown.

[0036] Figure 7 The graph shows the relationship between pH drift and dyeing rate for Examples 1, 3, and 11.

[0037] Figure 8 The chart shows the fracture strength retention rate of Example 1, Comparative Example 7, and Comparative Example 8.

[0038] Figure 9 This is a comparison of macroscopic optical photographs of the final product of Example 1 and the final product of Comparative Example 9; wherein, Figure 9 Figure a in the image is a macroscopic optical photograph of the dyed and finished polyester fabric obtained in Example 1; Figure 9 Figure b in the figure is a macroscopic optical photograph of the dyed and finished polyester fabric obtained in Comparative Example 9.

[0039] Figure 10 The images show a comparison of the SEM morphology of the final product of Example 1 and the final product of Comparative Example 9; where, Figure 10Figure a in the image is a low-magnification SEM image of the final product of Example 1; Figure 10 Figure b in the figure is a low-magnification SEM image of the final product of Comparative Example 9; Figure 10 Figure c in the image is a medium-magnification SEM image of the final product of Example 1; Figure 10 Image d in the figure is a medium-magnification SEM image of the final product of Comparative Example 9; Figure 10 Image e in the figure is a high-magnification SEM image of the final product of Example 1; Figure 10 Figure f in the image is a high-magnification SEM image of the final product of Comparative Example 9. Detailed Implementation

[0040] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings.

[0041] Example 1 A low-ratio aqueous dyeing and finishing composition was prepared as follows and used for dyeing and finishing polyester woven fabrics: S1: To prepare sodium sulfonate-based polyester-polyether copolymer, commercially available dimethyl terephthalate and 5-sulfonate dimethyl isophthalate, both with a purity ≥99%, are added to a reactor equipped with stirring, nitrogen introduction, methanol collection, and a vacuum interface at a molar ratio of 95:5; ethylene glycol is added, with a molar ratio of ethylene glycol to the total molar amount of the two dimethyl esters of 1.60:1; polyethylene glycol with a number average molecular weight of 400 g / mol is added, with the amount of polyethylene glycol being 5.00 wt% of the total mass of the two dimethyl esters; then tetrabutyl titanate is added, with the amount of tetrabutyl titanate being 0.02 wt% of the total mass of all reactive raw materials. Under nitrogen purity ≥99.9%, the mixture was mechanically stirred at 300 rpm for 30 min, heated to 160℃ and reacted for 2.00 h while continuously collecting methanol. When the methanol distillation rate reached 70.00% of the theoretical methanol distillation rate, the temperature was raised to 210℃ and polycondensed for 1.00 h under an absolute pressure of 5000 Pa in the reactor. After discharge, the material was cooled to 25℃, pulverized to particles that could pass through an 80-mesh sieve, and dried at 60℃ and 0.010 MPa for 4.00 h to obtain a sodium sulfonate-based polyester-polyether copolymer.

[0042] S2: To prepare an aqueous dispersion of the composite dispersed particles, 100 parts by weight of Disperse Red 60 parts by weight of the sodium sulfonate-based polyester-polyether copolymer prepared in this example and deionized water were mixed to adjust the solid content to 10.00 wt%. Acetic acid and anhydrous sodium acetate were added to adjust the pH of the system to 5.00. The mixture was sheared at 1000 rpm for 0.50 h at 15 °C, and then wet-milled at 5 m / s linear velocity for 0.50 h at 15 °C using zirconia beads with a particle size of 0.10 mm as the grinding medium. After milling, the mixture was filtered through a 100-mesh filtration to obtain an aqueous dispersion of the disperse dye-sodium sulfonate-polyether copolymer composite dispersed particles. In this example, the aqueous dispersion had a solid content of 10.00 wt%, a pH of 5.00, a composite dispersed particle D50 of 100 nm, a PDI of 0.10, and a mass ratio of disperse dye to sodium sulfonate-polyether copolymer of 100:10.

[0043] S3: Prepare an aqueous dyeing and finishing composition by mixing the aqueous dispersion of the composite dispersed particles prepared in this embodiment, acetic acid, anhydrous sodium acetate, and deionized water to obtain the aqueous dyeing and finishing composition.

[0044] S4: Dyeing of polyester woven fabric. Take 1000g of polyester woven fabric with a weight of 100g / m², which has been desized and scouring, as the dyeing material. Prepare a dye bath by adding the aqueous dyeing and finishing composition of this embodiment to deionized water. Adjust the pH of the dye bath to 4.50 using acetic acid and anhydrous sodium acetate, ensuring that the amount of Disperse Red 60 is 0.10wt% of the polyester woven fabric mass, and the liquor ratio is 1:5. Place the polyester woven fabric in the dye bath and heat it to 120℃ at 0.80℃ / min in a pressure dyeing device, holding it at this temperature for 30min. After holding, cool it down at 1℃ / min and drain the liquid. Wash it with deionized water at 60℃ for 5min, repeating the washing once. Dry the washed polyester woven fabric with hot air at 100℃ for 1min, then set it at 160℃ for 20s to obtain the dyed and finished polyester fabric.

[0045] S5: Quality Inspection Methods and Results. The dynamic light scattering method was used to determine the D50 and PDI of the composite dispersed particles. Before testing, the particles were diluted with deionized water to a solid content of 0.10 wt%. Each sample was tested three times. The pH of the dye bath was measured using a pH meter. The gray scale was used to evaluate the color fastness to washing and rubbing. The test results were as follows: D50 of the composite dispersed particles was 100±4 nm, PDI was 0.10±0.01, dye bath pH was 4.50±0.03, and the color fastness to washing, dry rubbing, and wet rubbing of the dyed polyester fabric was grade 4, grade 4, and grade 3, n=3. If the operating temperature fluctuates by more than ±2℃, the D50 and dye bath pH should be reconfirmed before dyeing.

[0046] Features and application scenarios of this embodiment: This embodiment adopts a relatively conservative low ratio scheme. The composite dispersed particles, dye dosage, liquor ratio, heating rate, dyeing temperature, washing temperature, drying temperature and setting temperature are all in the low range, which is suitable for light-colored polyester woven fabrics, low-energy dyeing and finishing and small-batch process establishment.

[0047] Example 2 For the raw materials and reaction configuration, this embodiment uses 1000g of polyester knitted fabric with a weight of 200g / m² as the dyeing and finishing object. The polyester knitted fabric is scouring and pre-setting treatment before dyeing. Disperse Blue 79 is selected as the disperse dye, and the disperse dye is a commercially available dye-grade raw material. Dimethyl terephthalate, sodium 5-sulfonate dimethyl isophthalate, ethylene glycol, polyethylene glycol, tetrabutyl titanate, acetic acid, anhydrous sodium acetate, sodium dithionite, and sodium hydroxide are all commercially available chemicals.

[0048] The sodium sulfonate-based polyester-polyether copolymer was prepared by adding dimethyl terephthalate and sodium 5-sulfonate isophthalate to a reactor at a molar ratio of 70:30. Ethylene glycol was added, with a molar ratio of ethylene glycol to the total molar amount of the two dimethyl esters of 2.40:1. Polyethylene glycol with a number average molecular weight of 4000 g / mol was added, at a rate of 30.00 wt% of the total mass of the two dimethyl esters. Tetrabutyl titanate was added, at a rate of 0.20 wt% of the total mass of all reactive raw materials. Under nitrogen protection (purity ≥99.9%), the mixture was mechanically stirred at 500 rpm for 40 min and reacted at 200℃ for 5.00 h. Methanol was collected. When the methanol distillation rate reached 95.00% of the theoretical methanol distillation rate, the temperature was raised to 245℃, and polycondensation was carried out at an absolute pressure of 100 Pa in the reactor for 4.00 h. After cooling, the material is pulverized and dried at 90℃ and 0.001MPa for 12.00h to obtain sodium sulfonate-based polyester-polyether copolymer.

[0049] The composite dispersion particles and dye bath were prepared by mixing 100 parts by weight of Dispersible Blue 79 and 80 parts by weight of sodium sulfonate-based polyester-polyether copolymer with deionized water to achieve a solid content of 35.00 wt%. Acetic acid and anhydrous sodium acetate were added to adjust the pH of the system to 7.00, and the mixture was sheared at 8000 rpm for 2.00 h at 45 °C. Subsequently, using zirconia beads with a particle size of 1.00 mm as the grinding medium, the mixture was wet-milled at 15 m / s linear velocity at 45 °C for 4.00 h. After filtration through a 400 mesh, an aqueous dispersion of the composite dispersion particles was obtained. The aqueous dispersion had a solid content of 35.00 wt%, a pH of 7.00, a D50 of 350 nm, and a PDI of 0.35. The aqueous dispersion of the composite dispersion particles, acetic acid, anhydrous sodium acetate, and deionized water were mixed to obtain an aqueous dyeing and finishing composition.

[0050] Dyeing, reduction cleaning, and setting: A water-based dyeing and finishing composition was added to deionized water to prepare the dye bath. The pH of the dye bath was adjusted to 5.80 using acetic acid and anhydrous sodium acetate. The amount of Disperse Blue 79 was 6.00 wt% of the polyester knitted fabric, with a liquor ratio of 1:15. The polyester knitted fabric was placed in the dye bath and heated to 135℃ at a rate of 2.00℃ / min in a pressure dyeing apparatus, and held at this temperature for 60 min. After holding, the temperature was lowered at a rate of 3℃ / min and the liquid was drained. The fabric was then washed with deionized water at 90℃ for 20 min, repeated three times. The washed polyester knitted fabric underwent reduction cleaning. The reduction cleaning solution contained 2.00 g / L sodium dithionite and 2.00 g / L sodium hydroxide, and the treatment was carried out at 85℃ for 20 min. After reduction cleaning, the fabric was washed with deionized water at 80℃ for 15 min. The treated polyester knitted fabric was dried at 130℃ for 5 minutes using infrared drying, and then set at 185℃ for 90 seconds to obtain the dyed and finished polyester fabric.

[0051] Quality testing methods and results: Dynamic light scattering method was used to determine the D50 and PDI of the composite dispersed particles; a pH meter was used to determine the pH of the dye bath; and a gray scale was used to evaluate the color fastness of the dyed and finished fabrics. The test results were as follows: D50 of the composite dispersed particles was 350±9 nm, PDI was 0.35±0.02, dye bath pH was 5.80±0.04, and the color fastness of the dyed polyester knitted fabric to soap washing was grade 4-5, the color fastness to dry rubbing was grade 4-5, and the color fastness to wet rubbing was grade 4, n=3. The reducing cleaning solution should be prepared and used immediately, and deionized water rinsing should be performed immediately after treatment to reduce the impact of residual alkali on the fabric's hand feel.

[0052] Features of the solution in this embodiment This embodiment adopts an optimized scheme with a relatively high load. The composite dispersed particles, dye dosage, dyeing temperature, heat preservation time, washing intensity, reduction washing intensity and setting conditions are all in a high range, which is suitable for high fastness dyeing and finishing of medium-dark or dark polyester knitted fabrics.

[0053] Example 3 In this embodiment, 1000g of polyester nonwoven fabric with a basis weight of 50g / m² was selected as the treatment object. The polyester nonwoven fabric was first scouring and pre-dried in hot air at 90℃ for 2 minutes, and then proceeded to the dyeing step. Disperse Orange 30 was selected as the disperse dye, and the number average molecular weight of polyethylene glycol was 1500g / mol.

[0054] I. Preparation of Sodium Sulfonate-Based Polyester-Polyether Copolymer: Dimethyl terephthalate and sodium 5-sulfonate dimethyl isophthalate were mixed at a molar ratio of 85:15. Ethylene glycol was added, with a molar ratio of ethylene glycol to the total molar amount of the two dimethyl esters of 2.00:1. Polyethylene glycol was added at a rate of 15.00 wt% of the total mass of the two dimethyl esters. Tetrabutyl titanate was added at a rate of 0.10 wt% of the total mass of all reactive raw materials. Under nitrogen protection, the mixture was mechanically stirred at 400 rpm for 35 min and reacted at 180 °C for 3.50 h. Methanol was collected. When the methanol distillation rate reached 85.00% of the theoretical methanol distillation rate, the temperature was raised to 225 °C, and polycondensation was carried out in the reactor at an absolute pressure of 1000 Pa for 2.50 h. The material was discharged, cooled, pulverized, and dried at 75℃ and 0.005MPa for 8.00h to obtain sodium sulfonate-based polyester-polyether copolymer.

[0055] II. Preparation of Composite Dispersion Particles: 100 parts by weight of Dispersion Orange and 30-40 parts by weight of sodium sulfonate-based polyester-polyether copolymer were mixed with deionized water, and the solid content was adjusted to 22.00 wt%. Acetic acid and anhydrous sodium acetate were added to adjust the pH of the system to 6.00. The mixture was sheared and dispersed at 4500 rpm for 1.20 h at 30 °C, and then wet-milled at 10 m / s linear velocity for 2.00 h at 30 °C using zirconia beads with a particle size of 0.50 mm as the grinding medium. After filtration through a 200-mesh filtration system, an aqueous dispersion of composite dispersion particles was obtained. The aqueous dispersion had a solid content of 22.00 wt%, a pH of 6.00, a D50 of 220 nm, and a PDI of 0.22.

[0056] III. Aqueous Dyeing and Finishing Composition and Dye Bath: The aqueous dispersion of the composite dispersed particles, acetic acid, anhydrous sodium acetate, and deionized water are mixed to obtain the aqueous dyeing and finishing composition. The aqueous dyeing and finishing composition is added to deionized water to prepare the dye bath. The pH of the dye bath is adjusted to 4.80 using acetic acid and anhydrous sodium acetate, and the amount of Disperse Orange 30 is 0.50 wt% of the polyester nonwoven fabric, with a bath ratio of 1:6.

[0057] IV. Dyeing and Finishing: The polyester nonwoven fabric is placed in a dye bath and heated to 125℃ at a rate of 1.00℃ / min in a pressure dyeing apparatus, and held at this temperature for 35 minutes. After the holding period, the temperature is lowered at a rate of 1℃ / min and the liquid is drained. The fabric is then washed with deionized water at 60℃ for 5 minutes, and this washing process is repeated once. The washed polyester nonwoven fabric is then dried at 100℃ for 1 minute using a pad-drying method, and then set at 165℃ for 30 seconds to obtain the dyed and finished polyester fabric.

[0058] V. Quality Inspection Methods and Results: The D50 and PDI of the composite dispersed particles were determined using dynamic light scattering, the pH of the dye bath was measured using a pH meter, the color difference at different locations of the same batch of samples was measured using a colorimeter, and color fastness was evaluated using a gray scale. The test results were as follows: Composite dispersed particle D50 was 220±6 nm, PDI was 0.22±0.01, dye bath pH was 4.80±0.03, color difference ΔE at different locations of the fabric was 0.85±0.07, color fastness to washing was grade 4, color fastness to dry rubbing was grade 4-5, color fastness to wet rubbing was grade 4, n=3. Nonwoven fabrics should be kept flat and unfolded before entering the dye bath to reduce dyeing differences caused by local folding.

[0059] The process features and application directions of this embodiment: This embodiment adopts a low-value region combination of the preferred process. The dye dosage, liquor ratio, heating rate, dyeing temperature, holding time and setting conditions are all relatively mild, which is suitable for lightweight polyester nonwoven fabrics and light to medium color dyeing and finishing with high requirements for dimensional stability.

[0060] Example 4 This embodiment provides a dyeing and finishing method for high-grammage polyester woven fabrics. The processing scale is 1000g, and the polyester woven fabric has a grammage of 300g / m². Before entering the dye bath, the fabric undergoes desizing, scouring, and pre-setting treatments in sequence. The disperse dye used is a mixture of Disperse Red 60 and Disperse Blue 56 in a mass ratio of 1:1, and the polyethylene glycol has a number-average molecular weight of 3000g / mol.

[0061] The preparation process first involves the synthesis of sodium sulfonate-based polyester-polyether copolymer. Dimethyl terephthalate and sodium 5-sulfonate isophthalate are added to a reactor at a molar ratio of 80:20. Ethylene glycol is then added, with a molar ratio of ethylene glycol to the total molar amount of the two dimethyl esters of 1.80:1. Polyethylene glycol is added at a rate of 20.00 wt% of the total mass of the two dimethyl esters. Tetrabutyl titanate is then added at a rate of 0.15 wt% of the total mass of all reactive raw materials. Under nitrogen protection, the mixture is mechanically stirred at 450 rpm for 35 min and reacted at 190 °C for 4.00 h. After the methanol distillation reaches 90.00% of the theoretical methanol distillation, the temperature is raised to 235 °C, and polycondensation is carried out at an absolute pressure of 500 Pa in the reactor for 3.00 h. After the reactants were discharged and cooled, they were pulverized and dried at 80℃ and 0.003MPa for 10.00h to obtain sodium sulfonate-based polyester-polyether copolymer.

[0062] Subsequently, an aqueous dispersion of composite dispersed particles was prepared by mixing 100 parts by weight of a mixed disperse dye, 65 parts by weight of a sodium sulfonate-based polyester-polyether copolymer, and deionized water to achieve a solid content of 28.00 wt%. Acetic acid and anhydrous sodium acetate were added to adjust the pH of the system to 5.50. The mixture was sheared at 6500 rpm for 1.50 h at 25 °C, and then wet-milled at 12 m / s linear velocity for 3.00 h at 25 °C using 0.30 mm zirconia beads as the grinding medium. The resulting aqueous system was filtered through a 300-mesh filtration system to obtain an aqueous dispersion of composite dispersed particles with a D50 of 150 nm and a PDI of 0.18.

[0063] Aqueous dispersion of the composite dispersed particles, acetic acid, anhydrous sodium acetate, and deionized water were mixed to obtain an aqueous dyeing and finishing composition. The aqueous dyeing and finishing composition was added to deionized water to prepare a dye bath. The pH of the dye bath was adjusted to 5.50 using acetic acid and anhydrous sodium acetate, ensuring the total amount of mixed disperse dye was 4.00 wt% of the polyester woven fabric, with a bath ratio of 1:10. The polyester woven fabric was placed in the dye bath and heated to 132°C at a rate of 1.50°C / min in a pressure dyeing apparatus, and held at this temperature for 50 min. After holding, the temperature was lowered at a rate of 3°C / min and the liquid was drained. The fabric was then washed with deionized water at 85°C for 15 min, repeated three times. The washed polyester woven fabric underwent a reduction wash at 70°C for 5 min, using sodium dithionite (0.50 g / L) and sodium hydroxide (0.50 g / L). After the reduction wash, the fabric was washed with deionized water at 50°C for 5 min. After cleaning, the polyester woven fabric is dried at 120℃ for 3 minutes by hot air drying, and then set at 178℃ for 60 seconds to obtain dyed and finished polyester fabric.

[0064] Quality testing was conducted using dynamic light scattering, a pH meter, a colorimeter, and a gray scale. The results were as follows: composite dispersed particle D50 was 150±5 nm, PDI was 0.18±0.01, dye bath pH was 5.50±0.03, color difference ΔE at different locations on the fabric was 0.78±0.06, color fastness to washing was grade 4-5, color fastness to dry rubbing was grade 4-5, color fastness to wet rubbing was grade 4, and n=3. If localized moisture content differences exist on the fabric surface after setting, the color difference evaluation should be repeated after extending the hot air equilibration period by 1 minute.

[0065] The applicable scenario for this embodiment: This embodiment adopts a combination of relatively high load and optimized finishing conditions, taking into account higher dye usage, higher content of composite dispersed particles, mild reduction cleaning and strong setting treatment, which is suitable for batch dyeing and finishing of high weight medium dark polyester woven fabrics.

[0066] Comparative Example 1: Basically the same as Example 1, except that the amount of sodium sulfonate-based polyester-polyether copolymer in step S2 is adjusted to 5 parts by mass, and the mass ratio of disperse dye to sodium sulfonate-based polyester-polyether copolymer is 100:5; except for the above differences, the other preparation and dyeing and finishing conditions are the same as in Example 1.

[0067] Comparative Example 2: Basically the same as Example 1, except that when preparing the dye bath in S4, the amount of Disperse Red 60 was adjusted to 0.05 wt% of the polyester woven fabric mass; apart from the above differences, the other preparation and dyeing and finishing conditions were the same as in Example 1.

[0068] Comparative Example 3: It is basically the same as Example 1, except that when preparing the dye bath in S4, the pH of the dye bath is adjusted to 6.30; apart from the above differences, the other preparation and dyeing conditions are the same as those in Example 1.

[0069] Comparative Example 4: Basically the same as Example 1, except that the bath ratio was adjusted to 1:20 during S4 dyeing; apart from the above differences, the other preparation and dyeing conditions were the same as in Example 1.

[0070] Comparative Example 5: Basically the same as Example 1, except that the heating rate was adjusted to 0.40℃ / min during S4 staining; apart from the above differences, the other preparation and dyeing conditions were the same as in Example 1.

[0071] Comparative Example 6: It is basically the same as Example 1, except that the holding time at 120°C was adjusted to 20 min during S4 staining; apart from the above differences, the other preparation and dyeing conditions are the same as those in Example 1.

[0072] Comparative Example 7: Basically the same as Example 1, except that during S4 cleaning, deionized water was used to clean at 50°C for 5 minutes; apart from the above differences, the other preparation and dyeing and finishing conditions were the same as in Example 1.

[0073] Comparative Example 8: It is basically the same as Example 1, except that the setting temperature is adjusted to 150°C and the setting time is kept at 20s during the S4 setting process; apart from the above differences, the other preparation and dyeing and finishing conditions are the same as those in Example 1.

[0074] Comparative Example 9: Essentially the same as Example 1, except that sodium sulfonate-based polyester-polyether copolymer was not added in step A1. Instead, 100 parts by weight of Disperse Red 60 were mixed with deionized water and subjected to pH adjustment, pre-dispersion, wet grinding, and filtration. Apart from the above differences, the remaining preparation and dyeing / finishing conditions were the same as in Example 1. This comparative example was used to investigate the synergistic relationship between the disperse dye and the sodium sulfonate-based polyester-polyether copolymer.

[0075] Comparative Example 10: Essentially the same as Example 1, except that in step A1, the sodium sulfonate-based polyester-polyether copolymer was replaced with a polyester-polyether copolymer without the dimethyl isophthalate (5-sulfonate) structural unit. This polyester-polyether copolymer was prepared from dimethyl terephthalate, ethylene glycol, and polyethylene glycol with a number average molecular weight of 400 g / mol under the temperature, time, pressure, and drying conditions of Example 1. Except for the above differences, the preparation and dyeing / finishing conditions were the same as in Example 1. This comparative example was used to investigate the synergistic relationship between the sodium sulfonate-based structural unit and the polyether segment.

[0076] Comparative Example 11: Essentially the same as Example 1, except that the sequential control of A2 followed by A3 was omitted during the preparation of the composite dispersed particles. First, Dispersion Red 60, sodium sulfonate-based polyester-polyether copolymer, and deionized water were wet-milled at 5 m / s for 0.50 h at 15°C. Then, acetic acid and anhydrous sodium acetate were added to adjust the pH of the system to 5.00. Subsequently, the mixture was sheared and dispersed at 1000 rpm for 0.50 h at 15°C and filtered through a 100-mesh filtration system. Except for the above differences, the remaining preparation and dyeing / finishing conditions were the same as in Example 1. This comparative example was used to examine the synergistic relationship between pH adjustment, pre-dispersion, and the order of wet milling.

[0077] Characterization and performance testing: The aqueous dispersions of the composite dispersed particles in Examples 1-4 and Comparative Examples 1-11 were tested for D50, PDI, and dispersion stability to evaluate the effect of sodium sulfonate-based polyester-polyether copolymer on the particle size control and anti-agglomeration ability of dye particles after composite dispersion. Dynamic light scattering was used. The samples were diluted with deionized water to a solid content of 0.10 wt%, equilibrated at 25°C for 10 min, and each sample was measured three times. The average D50, standard deviation of D50, average PDI, and standard deviation of PDI were recorded. D50 is the median particle size distribution, and PDI is the polydispersity index. The sample was then allowed to stand at 25°C for 24 hours. Samples were taken from the same sampling position on the upper layer of the same standing container at the beginning of the standing process and again after 24 hours. The absorbance was measured at the characteristic absorption wavelength of the corresponding disperse dye. The absorbance retention rate of the upper layer was calculated as follows: 24-hour dispersion retention rate = A24h / A0 × 100%, where A0 is the absorbance at the beginning of the standing process and A24h is the absorbance after 24 hours of standing. A higher value indicates better dispersion stability.

[0078] The pH stability and dye uptake of the dye baths in Examples 1-4 and Comparative Examples 1-11 were tested to evaluate the effect of the acetic acid / anhydrous sodium acetate buffer system on the stability of the dyeing process. Samples were taken before dyeing, at the target temperature, and at the end of the holding period, and the pH of the dye bath was measured at the same test temperature. The difference between the maximum and minimum pH values ​​at each time point was taken as the pH drift value. Dye solutions were taken before and after dyeing. For dye baths containing one disperse dye, the solution was diluted with deionized water by the same dilution factor, and the absorbance was measured at the characteristic absorption wavelength of the disperse dye. For mixed dye baths containing two disperse dyes, the absorbance was measured at the characteristic absorption wavelengths of the two disperse dyes respectively. The total uptake was calculated by weighting the proportion of each disperse dye by its mass. The uptake of each disperse dye was calculated as uptake = (A0-A1) / A0 × 100%, where A0 is the absorbance of the dye solution before dyeing, and A1 is the absorbance of the residual solution after dyeing. The data fields are pH drift value, average dye uptake rate, and standard deviation of dye uptake rate. The lower the pH drift value and the higher the dye uptake rate, the better the dye bath control effect. n=3.

[0079] The dyeing uniformity of the polyester fabrics from Examples 1-4 and Comparative Examples 1-11 was tested to evaluate the effects of composite dispersed particles, dye bath pH, ​​liquor ratio, and heating rate on fabric color difference. Each fabric was conditioned in a standard light source box for 24 hours. The L, a, and b values ​​were measured at five positions (left, center, right, top, and bottom) on the fabric surface using a portable colorimeter. The average L, a, and b values ​​at these five positions were used as a reference to calculate the color difference ΔE at each position, and the maximum value was taken as the dyeing uniformity ΔE for that fabric. The average and standard deviation of the dyeing uniformity ΔE for three parallel fabrics were also calculated. Units are dimensionless; lower values ​​indicate better dyeing uniformity. n=3.

[0080] The color fastness to washing was determined for the dyed and finished polyester fabrics of Examples 1-4 and Comparative Examples 1-11 to evaluate the dye retention ability in the fabric after washing and setting. Tests were conducted according to GB / T3921-2008 "Textiles - Tests for color fastness to washing". Color change and staining grades were recorded, and a gray scale was used for grading. Each sample was tested in triplicate, and the standard grade obtained from each test was recorded separately. The color fastness grade codes were not used as continuous numerical values ​​for calculating the arithmetic mean and standard deviation.

[0081] The color fastness to rubbing of the dyed and finished polyester fabrics of Examples 1-4 and Comparative Examples 1-11 was determined to evaluate the residual dye on the fabric surface and the state of dye binding under dry and wet rubbing conditions. Dry and wet rubbing tests were conducted according to GB / T3920-2008 "Textiles - Tests for Color Fastness - Color Fastness to Rubbing". The gray scale grades were recorded. Each sample was tested in triplicate, and the standard grade obtained from each test was recorded. The color fastness grade code was not used as a continuous numerical value for calculating the arithmetic mean and standard deviation. When the grades of the three parallel tests were consistent, Table 1 was abbreviated as the consistent grade; when the grades of the three parallel tests were inconsistent, Table 1 listed the fixed grade obtained from the three tests in the order of testing.

[0082] The breaking strength retention rate of the dyed and finished polyester fabrics in Examples 1-4 and Comparative Examples 1-11 was tested to evaluate the effects of washing, reduction washing, and setting conditions on the structural integrity of the fabrics. The fabrics before and after dyeing and finishing were conditioned for 24 hours at 25°C and 65% relative humidity. Warp and weft samples of woven and knitted fabrics, or longitudinal and transverse samples of nonwoven fabrics, were cut. The breaking strength was measured using a fabric strength tester at a tensile speed of 100 mm / min. The breaking strength retention rate was calculated as: breaking strength retention rate = (breaking strength after dyeing and finishing / breaking strength before dyeing and finishing) × 100%. The average breaking strength retention rate and the standard deviation of the breaking strength retention rate were obtained experimentally, in percentage (%). Higher values ​​indicate better fabric structure retention. n=3.

[0083] To verify the effectiveness of the high-fastness dyeing and finishing process for polyester fabrics of the present invention, using Example 1 as the baseline system, a systematic investigation was conducted on the key process parameters affecting dye dispersion stability, dye migration uniformity, color fastness, and fabric structure retention. In Example 1, disperse dyes and sodium sulfonate-based polyester-polyether copolymers formed composite dispersed particles, and dyeing, washing, drying, and setting were completed in an acetic acid / anhydrous sodium acetate weak acid buffer system. By controlling factors such as copolymer dosage, dye bath pH, ​​composite dispersed particle size, and setting temperature, it can be demonstrated that the present invention does not simply rely on increasing the amount of dispersant or enhancing the intensity of post-treatment to improve the dyeing and finishing effect, but rather achieves high-fastness dyeing and finishing through the synergistic matching of dispersion protection, dye migration, floating color removal, and fiber structure protection.

[0084] First, to clarify the impact of sodium sulfonate-based polyester-polyether copolymers on the stability of disperse dye systems, in Figure 1In the experiments shown, based on Example 1, only the mass fraction of the sodium sulfonate-based polyester-polyether copolymer was changed, set to 5, 10, 25, 45, 60, 80, and 95 parts, while the other dispersion, dyeing, washing, and setting conditions remained the same. The results showed that when the copolymer content increased from 5 parts to 10-60 parts, the 24-hour dispersion retention rate increased from approximately 72.6% to 91.8%-96.0%. This result is consistent with the design of the sodium sulfonate groups providing electrostatic stabilization and the polyester-polyether segments improving the interfacial compatibility between the disperse dye particles and the dye bath medium, indicating that an appropriate amount of copolymer is beneficial for maintaining high dispersion stability of the dye in the dye bath.

[0085] but, Figure 1 The results also showed that when the copolymer dosage was increased to 95 parts, the 24-hour dispersion retention rate decreased. This phenomenon indicates that a higher copolymer dosage is not necessarily better; excessive copolymer may alter the particle interface state and the rheological state of the system, which is detrimental to maintaining the stability of the composite dispersion system. Therefore, controlling the dosage of sodium sulfonate-based polyester-polyether copolymer within an appropriate range is beneficial for obtaining better dispersion protection.

[0086] Furthermore, to investigate the effect of the acidity or alkalinity of the dye bath on the uniformity of dyeing, in Figure 2 In the experiments shown, based on Example 1, only the dye bath pH was adjusted to 4.20, 4.50, 4.80, 5.15, 5.50, 5.80, and 6.10, while the remaining formulation composition, dye concentration, heating program, and holding time remained consistent. The results showed that when the dye bath pH was within the weakly acidic range of 4.50-5.80, the dyeing uniformity index ΔE remained at approximately 0.72-1.12, indicating that this pH range is beneficial for maintaining a relatively stable interaction between the disperse dye, the sodium sulfonate-based polyester-polyether copolymer, and the polyester fibers. A weakly acidic environment helps reduce the dyeing differences caused by local pH fluctuations during the dyeing process, allowing the dye to migrate into the fabric at a more uniform rate.

[0087] When the pH of the dye bath is too low or too high Figure 2 The ΔE value increased significantly. The above results indicate that, under the conditions of this experiment, controlling the pH of the dye bath within the range of 4.50-5.80 is beneficial to maintaining a low staining uniformity ΔE.

[0088] Regarding the dispersed particle structure, Figure 3Based on Example 1, disperse dye-sodium sulfonate-polyester-polyether copolymer composite dispersed particles with median particle sizes D50 of 80, 100, 150, 220, 280, 350, and 420 nm were prepared, with the remaining formulation composition and dyeing conditions remaining consistent for each sample. The results showed that when D50 was 100-350 nm, the dispersion retention rate remained at approximately 89.6%-95.2% after 24 hours, and the dyeing uniformity ΔE was approximately 0.78-1.15, indicating that the composite dispersed particles within this particle size range possess both good suspension stability and dye migration ability. When the particle size is within a suitable range of nanometer to submicron, the particles are less prone to stratification of the dye bath concentration due to sedimentation under their own weight, and are also less likely to generate strong surface energy-driven agglomeration due to excessively high specific surface area. Therefore, a relatively uniform dye supply can be maintained throughout the dyeing process.

[0089] In contrast, when D50 decreases to 80 nm, although the particle size is smaller, the surface energy of the particles increases, increasing the risk of secondary aggregation after particle collisions, leading to a decrease in dispersion retention and an increase in ΔE. When D50 increases to 420 nm, particle sedimentation and local enrichment tendencies are enhanced, resulting in uneven dye concentration distribution in the dye bath and consequently, localized differences in dyeing on the fabric surface. Therefore, this invention, by controlling the D50 of the composite dispersed particles within a suitable range of 100-350 nm, ensures that the dye particles possess both sufficient dispersion stability in the dye bath and maintain effective migration and diffusion into the polyester fibers, further solving the problem of simultaneously achieving dispersion stability and dyeing uniformity at the particle scale.

[0090] After optimizing the dispersion system and dye bath conditions, it is also necessary to verify the impact of the finishing and setting process on the structural stability of the fabric. Figure 4 Based on Example 1, only the setting temperature was set to 150, 160, 168, 172, 178, 185 and 195°C, while the other dyeing, washing and finishing conditions remained the same.

[0091] The results showed that the breaking strength retention rate was approximately 93.8%-95.6% within the 160-185℃ range, indicating that the fabric maintained a high breaking strength retention rate within this setting temperature range without significant mechanical property degradation. As shown in Table 1, Comparative Example 8, with a setting temperature of 150℃ and a setting time of 20 s, had a breaking strength retention rate of approximately 97.0%, but its color fastness to washing and dry rubbing were both grade 3-4, lower than grade 4 of Example 1. Therefore, the determination of the lower limit of the setting temperature in this invention is not solely based on the breaking strength retention rate, but rather considers both color fastness and fabric structure retention. Under the conditions of this experiment, setting temperatures above 160℃ are more conducive to obtaining a more balanced overall performance.

[0092] When the setting temperature rises to 195℃, the fabric breaking strength retention rate decreases, indicating that excessively high setting temperatures may adversely affect fiber structure, fabric dimensional state, or the stress state between yarns. Therefore, controlling the setting temperature within the range of 160-185℃ is beneficial for balancing dyeing and finishing fastness and fabric structural integrity.

[0093] To further verify that the above parameters do not act in isolation, but rather originate from the synergistic effect of the composite dispersion system, the weak acid buffer system, and process control of this invention, Figure 5 The 24-hour dispersion retention rates of Example 1, Comparative Example 9, and Comparative Example 11 were statistically compared. The results showed that the 24-hour dispersion retention rate of Example 1 was approximately 91.8%, significantly higher than the approximately 50.2% of Comparative Example 9 and approximately 65.8% of Comparative Example 11. Specifically, Comparative Example 9 did not include sodium sulfonate-based polyester-polyether copolymer, resulting in a lack of effective interfacial stabilization protection for the disperse dye. Consequently, the dye particles were more prone to sedimentation, flocculation, and stratification during settling, leading to a significantly lower dispersion retention rate. While Comparative Example 11 possessed some stabilizing conditions, it failed to achieve the same composite dispersion and dye bath synergistic environment as Example 1, and its dispersion retention rate remained significantly lower than that of Example 1. These results demonstrate that simply adjusting the dispersion conditions or dye bath conditions alone is insufficient to achieve the stabilizing effect of Example 1. Only through the combined action of disperse dye, sodium sulfonate-based polyester-polyether copolymer, particle size control, and a weakly acidic dye bath can a long-term stable dye dispersion system be obtained.

[0094] The stability of the pH of the dye bath during heating and heat preservation processes was further improved by... Figure 6 This has been verified. Figure 6 The pH changes of Examples 1, 3, and 11 before dyeing, at the target temperature, and at the end of the holding period were recorded. The results showed that the pH of Example 1 changed from approximately 4.50 to approximately 4.56, with an overall fluctuation of only about 0.06; the pH of Comparative Example 3 increased from approximately 6.30 to approximately 6.62, with a fluctuation of about 0.32; and the pH of Comparative Example 11 increased from approximately 4.50 to approximately 4.84, with a fluctuation of about 0.34. These results indicate that the acetic acid / anhydrous sodium acetate weak acid buffer system used in Example 1 can effectively suppress pH drift during the heating and holding processes, ensuring that the dye bath remains within the weak acid range suitable for the stable presence and uniform dyeing of disperse dyes. Although Comparative Example 3 also used acetic acid and anhydrous sodium acetate to adjust the staining bath, its initial pH was 6.30, deviating from the weakly acidic range of 4.50-5.80 defined in this invention. Comparative Example 11, while having an initial pH similar to Example 1, still exhibited significant pH drift during the staining process due to changes in the order of pH adjustment, pre-dispersion, and wet grinding. These results indicate that under the experimental conditions, using only acetic acid and anhydrous sodium acetate, or simply controlling the initial pH, is insufficient to achieve the overall process stability shown in Example 1.

[0095] Figure 7 The correlation between pH drift and dye uptake was further established. The results showed that the pH drift in Example 1 was approximately 0.06, with a dye uptake of approximately 86.5%; the pH drifts in Comparative Examples 3 and 11 were approximately 0.32 and 0.34, respectively, with dye uptakes of approximately 62.0% and 68.5%, respectively. Under the experimental conditions, a smaller pH drift corresponded to a higher dye uptake. Example 1 achieved a higher dye uptake under conditions of smaller pH drift, indicating that the weak acid buffer system not only improved dye bath stability but also enhanced dye utilization efficiency. Figures 5 to 7 It is evident that the present invention achieves synergistic effects in three aspects—static stability, process stability, and dyeing efficiency—through the combined use of composite dispersed particles and buffered dye baths, rather than relying on a single component or a single process to achieve localized improvements.

[0096] However, improving colorfastness at the expense of excessive soaping, strong alkaline reducing cleaning, or excessively high-temperature setting may lead to a decline in the mechanical properties of the fabric. To verify the protective effect of this invention on the structural integrity of the fabric, Figure 8 The fracture strength retention rates of Example 1, Comparative Example 7, and Comparative Example 8 were further compared. The results showed that the fracture strength retention rate of Example 1 was approximately 95.6%, that of Comparative Example 7 was approximately 96.4%, and that of Comparative Example 8 was approximately 97.0%, all three maintaining a high level.

[0097] To further verify the effect of the composite dispersion system of the present invention on improving the uniformity of dyeing and finishing at low ratios from a macroscopic appearance perspective, Figure 9 Macroscopic optical photographs were taken comparing the final product of Example 1 with the final product of Comparative Example 9. Figure 9 Image a is a macroscopic optical photograph of the dyed and finished polyester fabric obtained in Example 1. In this example, the polyester woven fabric had a basis weight of 100 g / m², the amount of Disperse Red 60 was 0.10 wt% of the fabric mass, the dye bath pH was 4.50, the liquor ratio was 1:5, and the fabric was treated with a heat treatment of 120°C for 30 min, a wash at 60°C for 5 min, a dry at 100°C for 1 min, and a set at 160°C for 20 s. Figure 9 As can be seen, even under the low ratio condition of only 0.10wt% of Disperse Red 60, the fabric as a whole still presents a continuous and uniform appearance from light red to red, and no obvious color spots, color dots or local deposition differences are observed. This shows that the water-based dyeing and finishing composition of the present invention can still maintain good dyeing and finishing uniformity under the conditions of mild dye dosage and low liquor ratio.

[0098] Figure 9 b is a macroscopic optical photograph of the dyed and finished polyester fabric obtained in Comparative Example 9. No sodium sulfonate-based polyester-polyether copolymer was added during its preparation, and the remaining dyeing and finishing conditions were consistent with those in Example 1. Figure 9 Compared to a, Figure 9In b, the fabric surface is more prone to uneven color, color spots, or local deposition differences, indicating that when there is a lack of copolymers involved in the compound dispersion, the stability of Disperse Red 60 in the dye bath is insufficient, and the dye particles are prone to local aggregation and uneven deposition on the fabric surface. Figure 9 Macroeconomic results and Figure 1 , Figure 3 and Figure 5 The results regarding copolymer dosage, particle size, and dispersion retention rate corroborate each other, indicating that the sodium sulfonate-based polyester-polyether copolymer, after participating in the composite dispersion, can significantly improve the uniformity of dye distribution in low-ratio dyeing and finishing systems, thereby improving the final fabric appearance consistency.

[0099] To further evaluate the impact of the composite dispersion system on the surface state of the fabric from the perspective of microstructure, Figure 10 The final product of Example 1 and the final product of Comparative Example 9 were compared by SEM. Figure 10 Image a is a low-magnification SEM image of the final product of Example 1. It can be observed that the warp and weft yarn structure of the polyester fabric after dyeing and finishing is clear, the surface state of the fabric is continuous over a large area, and no obvious blocky dye deposition or severe surface coverage is observed. It can be used as comparative information on the macroscopic morphology of the fabric surface. Figure 10 b is a low-magnification SEM image of the final product of Comparative Example 9. Compared with Example 1, the fabric surface of Comparative Example 9 is more prone to localized uneven deposition, indicating that the distribution stability of disperse dyes in the dye bath and on the fabric surface is poor when sodium sulfonate-based polyester-polyether copolymer is not added.

[0100] Figure 10 c is a medium-magnification SEM image of the final product of Example 1, which further shows that the overall surface of the yarn and polyester monofilament is relatively uniform, and can be used to compare the influence of the composite dispersion system on the local deposition state of the fiber surface. Figure 10 Image d is a medium-magnification SEM image of the final product of Comparative Example 9, used to compare and show that when no copolymer composite dispersion is used, dye particle residues or island-like deposition differences are more likely to appear on the fiber surface. This result, at the yarn and monofilament scale, reflects that Example 1 not only improved the macroscopic color uniformity of the fabric surface but also reduced dye accumulation and local concentration fluctuations at the microscopic scale.

[0101] Figure 10 e and Figure 10 f are high-magnification SEM images of the final product of Example 1 and the final product of Comparative Example 9, respectively, used to compare the granular adhesion and local aggregation morphology of the monofilament surfaces of the two. The monofilament surface of Example 1 is generally more continuous and uniform, while Comparative Example 9 is more prone to local granular aggregation. Figure 5The dispersion retention results shown for 24 h are consistent with the decreasing trend in dispersion stability when no sodium sulfonate-based polyester-polyether copolymer was added. These results can serve as supplementary evidence for evaluating the impact of the composite dispersion system on the surface condition of the fabric. The SEM images themselves are not used to determine the specific chemical composition of surface deposits.

[0102] In conclusion, Figure 1 The results showed that the copolymer dosage within an appropriate range was beneficial to improving the 24-hour dispersion retention rate, but the dispersion retention rate decreased when the dosage was further increased to 95 parts. Figure 2 The results showed that the staining uniformity ΔE was relatively low when the staining bath pH was 4.50-5.80; Figure 3 The results show that when D50 is 100-350nm, both high 24h dispersion retention and low staining uniformity ΔE can be obtained simultaneously. Figure 4 The results show that the fabric has a high rate of retention of breaking strength when set at 160-185℃. Figures 5 to 7 Further, it is shown that Example 1 has a higher 24-hour dispersion retention rate, less dye bath pH drift, and higher dye uptake compared to the comparative example. Table 1 lists the results of the colorfastness at the fixed level and... Figure 8 The results of the fracture strength retention rate shown collectively demonstrate that the present invention can maintain a high fracture strength retention rate while achieving high color fastness to soap washing, dry rubbing, and wet rubbing. Figure 9 and Figure 10 The results provide supplementary evidence from both macroscopic appearance and microscopic morphology perspectives, and the relevant differences in appearance and morphology are consistent with the changing trends of dispersion retention rate and staining uniformity.

[0103] Therefore, this invention, through the synergistic control of disperse dye-sodium sulfonate-polyester-polyether copolymer composite dispersion particles, acetic acid / anhydrous sodium acetate weak acid buffer system, and heating, washing, drying, and setting conditions, ensures that the dispersion protection effect does not excessively hinder dye migration, and that the floating color removal and dye stabilization processes do not excessively damage the polyester fabric structure. This achieves a synergistic improvement in dispersion stability, dyeing uniformity, color fastness, and fabric mechanical properties, effectively solving the technical pain points of existing polyester fabric dyeing and finishing processes where it is difficult to balance dispersion stability and dye migration uniformity, and where it is difficult to balance floating color removal and fabric structural integrity.

[0104] Table 1 Performance of Examples and Comparative Examples Note: D50, 24-hour dispersion retention rate, dyeing uniformity ΔE, and breaking strength retention rate are expressed as mean ± standard deviation, n=3; color fastness grades are fixed-level grading and are not calculated using arithmetic mean or standard deviation. When the results of three parallel color fastness tests are consistent, the table will abbreviate it as that consistent grade; when the results are inconsistent, the three grades will be listed in the order of testing, separated by " / ".

[0105] As can be seen from the performance of the examples and comparative examples in Table 1, Examples 1–4 show a relatively balanced trend among D50, 24h dispersion retention rate, dyeing uniformity, color fastness to soaping, color fastness to rubbing, and tensile strength retention rate. The conventional single-variable comparative examples show a decrease in dispersion stability, an increase in color difference, or a decrease in color fastness due to deviations from the set process in terms of composite dispersion particle content, dye bath pH, ​​bath ratio, heating rate, holding time, washing temperature, or setting temperature. In the synergistic comparative examples, after removing the sodium sulfonate-based polyester-polyether copolymer, replacing the copolymer structure, or changing the pH adjustment and grinding sequence, D50 increases, dispersion retention rate decreases, and color fastness decreases, indicating that the data trend is consistent with the technical logic of "synergistically balancing dispersion stability and dyeing uniformity".

[0106] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that any equivalent structural transformations made under the concept of the present invention and using the contents of the specification and drawings of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A high-fastness dyeing and finishing process for polyester fabrics, characterized in that, Includes the following steps: S1. A water-based dyeing and finishing composition is provided, the water-based dyeing and finishing composition comprising disperse dye-sodium sulfonate-polyester-polyether copolymer composite disperse particles, acetic acid, anhydrous sodium acetate and deionized water, wherein the mass ratio of disperse dye to sodium sulfonate-polyether copolymer in the composite disperse particles is 100:10-80, the D50 of the composite disperse particles is 100-350 nm, and the PDI is 0.10-0.35; S2. Preparation of dye bath: Add the aqueous dyeing and finishing composition to deionized water, and adjust the pH of the dye bath to 4.50-5.80 using acetic acid and anhydrous sodium acetate, so that the amount of disperse dye is 0.10-6.00 wt% of the polyester fabric mass; S3. Dyeing: Place the polyester fabric in the dye bath, with a bath ratio of 1:5 to 1:15 (based on the ratio of the mass of the polyester fabric to the mass of the dye bath), and heat to 120-135℃ at a rate of 0.80-2.00℃ / min, and hold for 30-60 minutes. S4. Cleaning: After cooling, drain the liquid and clean with deionized water at 60-90℃ for 5-20 minutes; S5. Drying and setting: Dry at 100-130℃ for 1-5 minutes, then set at 160-185℃ for 20-90 seconds to obtain dyed and finished polyester fabric.

2. The high-fastness dyeing and finishing process for polyester fabrics according to claim 1, characterized in that, The disperse dye is selected from one or more of Disperse Red 60, Disperse Blue 56, Disperse Blue 79 and Disperse Orange 30; The sodium sulfonate-based polyester-polyether copolymer is obtained by transesterification and polycondensation of dimethyl terephthalate, sodium 5-sulfonate dimethyl isophthalate, ethylene glycol and polyethylene glycol.

3. The high-fastness dyeing and finishing process for polyester fabrics according to claim 2, characterized in that, The dispersed dye-sodium sulfonate-polyether copolymer composite dispersed particles are prepared by the following steps: A1. Raw material preparation: Mix 100 parts by weight of disperse dye, 10-80 parts by weight of sodium sulfonate-based polyester-polyether copolymer, and deionized water, so that the solid content, based on the total mass of the disperse dye and the sodium sulfonate-based polyester-polyether copolymer as a percentage of the total mass of the mixture, is 10.00-35.00 wt%. A2. pH adjustment: Add acetic acid and anhydrous sodium acetate to adjust the pH of the system to 5.00-7.00; A3. Pre-dispersion: Shear dispersion at 1000-8000 rpm for 0.50-2.00 h at 15-45℃; A4. Wet grinding: using zirconia beads with a particle size of 0.10-1.00 mm as the grinding media, grinding at 15-45℃ and a linear velocity of 5-15 m / s for 0.50-4.00 h. A5. Post-treatment: Filter by 100-400 mesh to obtain an aqueous dispersion of disperse dye-sodium sulfonate-polyether copolymer composite dispersion particles; A6. Endpoint Criteria: The D50 of the composite dispersed particles in the aqueous dispersion is 100-350 nm, and the PDI is 0.10-0.

35.

4. The high-fastness dyeing and finishing process for polyester fabrics according to claim 2, characterized in that, The sodium sulfonate-based polyester-polyether copolymer is prepared by the following steps: B1. Raw material preparation: Dimethyl terephthalate and sodium 5-sulfonate dimethyl isophthalate are mixed at a molar ratio of 70-95:5-30, wherein the sum of their molar parts is 100; ethylene glycol is added, wherein the molar ratio of ethylene glycol to the total molar amount of dimethyl terephthalate and sodium 5-sulfonate dimethyl isophthalate is 1.60-2.40:1; polyethylene glycol is added, wherein the number average molecular weight of polyethylene glycol is 400-4000 g / mol, and the amount of polyethylene glycol used is 5.00-30.00 wt% of the total mass of dimethyl terephthalate and sodium 5-sulfonate dimethyl isophthalate. B2. Catalyst addition: Add tetrabutyl titanate in an amount of 0.02-0.20 wt% of the total mass of dimethyl terephthalate, sodium isophthalate 5-sulfonate, ethylene glycol, and polyethylene glycol in step B1. B3. Transesterification reaction: Under nitrogen protection, the reaction is carried out at 160-200℃ for 2.00-5.00h. Methanol is collected. When the amount of methanol distilled reaches 70.00-95.00% of the theoretical methanol distillation amount calculated based on the complete transesterification of the methyl groups of dimethyl terephthalate and sodium isophthalate 5-sulfonate, the polycondensation reaction begins. B4. Polycondensation reaction: Heat to 210-245℃ and react for 1.00-4.00 h under an absolute pressure of 100-5000 Pa in the reactor; B5. Post-processing: The discharged material is cooled, pulverized, and dried at 60-90℃ and 0.001-0.010MPa for 4.00-12.00h to obtain the sodium sulfonate-based polyester-polyether copolymer; B6. Composition parameters: Based on the molar ratio of dimethyl terephthalate and sodium 5-sulfonate dimethyl isophthalate, the theoretical structural unit content derived from sodium 5-sulfonate dimethyl isophthalate is 5.00-30.00 mol.

5. The high-fastness dyeing and finishing process for polyester fabrics according to claim 1, characterized in that, In S2, the amount of disperse dye used is 0.50-4.00 wt% of the polyester fabric mass.

6. The high-fastness dyeing and finishing process for polyester fabrics according to claim 1, characterized in that, In S2, the pH of the dye bath is 4.80-5.

50.

7. The high-fastness dyeing and finishing process for polyester fabrics according to claim 1, characterized in that, In S3, the liquor ratio is 1:6-1:10, the temperature is increased to 125-132℃ at 1.00-1.50℃ / min, and held for 35-50min.

8. The high-fastness dyeing and finishing process for polyester fabrics according to claim 1, characterized in that, After S4 cleaning, a reduction cleaning is performed using 0.50-2.00 g / L sodium dithionite and 0.50-2.00 g / L sodium hydroxide at 70-85°C for 5-20 min.

9. The high-fastness dyeing and finishing process for polyester fabrics according to claim 1, characterized in that, The weight of the polyester fabric is 50-300 g / m².

10. The high-fastness dyeing and finishing process for polyester fabrics according to claim 1, characterized in that, In S5, the setting temperature is 165-178℃ and the setting time is 30-60s.

Citation Information

Patent Citations

  • Dyeing process of polyester fabric

    CN111648140A